STUDI TENTANG GASTROINTESTINAL DISORDERS PADA WANITA YANG MENGALAMI STRES BISING PESAWAT UDARA DI SEKITAR BANDARA ADI SOEMARMO BOYOLALI - . Hartono (Wacana, 2014)
The interaction between aircraft noise stress factor with gastrointestinal disorders is believed through brain-HPA-axis, including psycho-neuro-immune-endocrinology system which is direct or indirect could influence on the acid secretion, motility, vascularitation and sensory of pain. The aims of the research is  to find out the difference of the gastrointestinal disorders of women with the aircraft  noise stress in the area of Adi Soemarmo Airport of Boyolali.The research finding is expected to contribute to the science development and to give benefits for local government and among people in the Area of Adi Soemarmo Airport in preventing the effect of aircraft noise. The research design was an analytical survey with a cross sectional approach, taking location at the Dibal and Gagak Sipat Village, Ngemplak Sub district, Boyolali District. The research was conducted from March 2011- to October 2011. The number of respondent was 117. They were divided into 3 groups; Group 1 was exposed 93.10 dB of noise level (39 respondents);  Group 2 was exposed 74.51 dB of noise level (38 respondents); and Group 3 was exposed  54.45 dB of noise level (40 respondents). The samples were taken using simple random sampling. The data were analyzed by Chi-kwadrat. Based on the results of the analysis, a conclusion was drawn that there was a significant difference of the gastrointestinal disorders of women with the aircraft  noise stress in the area of Adi Soemarmo Airport of Boyolali (p<0.05; α=0.05). Keywords : Aircraft noise stress, Gastrointestinal disorders, Adi Soemarmo Airport